PENCEGAHAN KARIES GIGI MELALUI SIKAT GIGI PADA PPA IQ-641 AGAPE SIKUMANA KOTA KUPANG - Pay, Mery Novaria; Ngadilah, Christina; Manu, Apri Adiari; Pinat, Leny Marlina A.; Eluama, Merniwati S. (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
Promotive and preventive actions in maintaining dental and oral health start from an early age. The indicator for maintaining dental and oral health is the time to brush your teeth because brushing your teeth is the main primary preventive measure. The effectiveness of brushing your teeth not only depends on the shape and method of brushing your teeth, but also depends on the frequency and duration of brushing your teeth. The aim of this community service is to provide information in the form of counseling on how to brush teeth properly and correctly to each individual so that they can maintain the health of their teeth and mouth and provide early preventive measures against caries in PPA IO-641 Agape Sikumana children through toothbrushing. The method used is in the form of counseling using a dental panthom model and practicing how to brush teeth properly and correctly, as well as supervision so that children can understand and get used to brushing their teeth correctly. The success of implementing this activity is marked by the child's ability to brush their teeth independently in the correct way so that tooth decay can be prevented. Result: counseling on how to brush teeth properly and correctly using a direct demonstration method using a dental panthom model to teach PPA children how to brush teeth correctly. This shows that it is important to provide dental health information in PPA so that children can understand the technique and how to brush their teeth properly and correctly. Conclusion: children aged 6-8 years have received promotive efforts in the form of education on how to brush their teeth properly and correctly as well as received preventive efforts in the form of brushing their teeth. Suggestion: It is hoped that PPA IO-641 Agape Sikumana can collaborate in dental health care services with the Dental Health Department to obtain routine promotive and preventive efforts so that newly erupted young permanent teeth are protected from caries